Social Media and Impression Management of Governors During the COVID-19 Pandemic - Rahmanto, Andre; Yuliarti, Monika Sri; Muhammad IN, Albert (KnE Social Sciences, 2022)
The COVID-19 pandemic has placed enormous demands on leaders in the public sector. Regional politicians have two interests: conveying information related to handling the pandemic and convincing the public that they are competent in handling the crisis. Through impression management on social media, regional leaders seek to achieve these two goals. This study aimed to find out what impression management tactics were used by regional heads in Indonesia during the pandemic through social media. This study used the Leader Impression Management Framework to analyze the contents of posts on the official Instagram accounts of four governors in Indonesia, namely West Java Governor Ridwan Kamil, DKI Jakarta Governor Anies Baswedan, Central Java Governor Ganjar Pranowo and East Java Governor Khofifah Indar Parawansa, during the early period of the pandemic. The results showed that the four governors used impression management tactics in varied ways, but there were similarities in the main tactics used to manage their impressions. The findings raised theoretical and practical implications about the leaders’ methods of communication to the public during the pandemic. Keywords: social media, impression management, leadership, governor, pandemic